Culture and city in debate: the case of Sobral, in northeast Brazil (2021)
To think about Brazilian cities is to think about a context of inequalities that is aggravated by regions. However, in the 2000s Brazilian economic growth allowed the development of the economically disadvantaged regions of the country, in the case of a northeastern region. And a city in the state of Ceará stands out, Sobral. In this article, we aim to analyze the culture and its resonances from the modifications in the urban space of Sobral and how these elements interfere with citizens’ lives.